COMPETENCY DEVELOPMENT STRATEGY OF BASIC EDUCATION SCHOOL DIRECTOR IN EDUCATION 4.0 - ครุธาโรจน์, มานะ; Siridhrungsri, Pinsuda; Suwan, Sanrasern (Journal of Buddhist Anthropology, 2020)
The objectives of research were: 1) study the components of the competency of basic education School Director in Education 4.0, 2) study the current situation and needs for competency development of Basic Education school administrators in Education 4.0 and 3) or competency development of Basic Education school administrators in Education 4.0. The mixed method research was employed. Quantitative research the sample group consisted of elementary school administrators. Under the Office of the Basic Education Commission, consisting of 314 people in the 6 regional inspection areas, academic year 2018, the research instrument was a qualitative research questionnaire the key informants are school administrators who perform best. Regarding the royal school of 7 persons, data were collected through in-depth interviews. Data were analyzed using descriptive statistics such as mean, percentage, standard deviation. And data synthesis by content analysis method the results of the research revealed that 1) The composition of the basic educational institution administrators' competency in the education era 4.0 consists of 4 aspects which are 1.1) characteristics 1.2) new age skills 1.3) academic leadership and 1.4) morality and ethics. 2) Nowadays, the strengths are moral courage. Ethics and code of ethics, etc., and the need to find that the most needed development is the use of media and information technology in school management. 3. The strategies for competency development of Basic Education school administrators in Education 4.0 consisted of 6 areas including 3.1)promoting the use of ICT among school administrators for institutional development, 3.2)developing English for communication and acquiring new knowledge, 3.3)optimizing the effectiveness of innovative management of school administrators for systematic institutional development, 3.4) supporting the potential of transformative leadership, 3.5)promoting the effectiveness of academic management of school administrators, and 3.6) developing school administrators to employ institutional management process based on good governance.